Tridimensional modelization of the impact of a vehicle against a metallic parking column at a low speed - Ferrer, B.; Ivorra, S.; Segovia, E.; Irles, R. (Engineering structures, 2010)
The accidental impact of a vehicle against a supporting structure represents a handicap in modeling the imposed loads for a building. The latest versions of building regulations worldwide incorporate recommendations related to this issue. Most of these recommendations suggest values for static loads equivalent to impacts with a given initial energy. However, the impact problem is inherently dynamic and besides the speed and mass of the vehicle, the behaviour of the car during the impact has a significant influence on the energy exchange between the vehicle and the structure. In this paper a critical review of the indications given in the EUROCODE is carried out. In order to achieve this, a series of static and dynamic simulations on finite elements have been designed and a realistic model for the car has been used. It has been shown that predictions of the standard in some sections are not very conservative and, therefore, its application could result in a damage of the structure.